PENGELOLAAN DANA INFAQ MASDJID BABBUL JANNAH KELURAHAN KENALI ASAM BAWAH DITINJAU DARI PERSPEKTIF EKONOMI ISLAM - Rohana (Manajemen Keuangan Syariah, 2023)
This research focuses on the transparency of financial management and economic development of the Babbul Jannah mosque which is located in the Kenali Asam Bawah sub-district, Kota Baru, Jambi. This research uses descriptive qualitative method. The informants in this study were the administrators of the Babbul Jannah mosque. The results obtained in this study are 1) For the Babbul Jannah mosque which stands in Kenali Asam, the management is still consumptive, such as renovating mosques, buying prayer mats, mukena, Al-Qur'an and so on. For productive things, the Babbul Jannah mosque only rents tents, for other productive things it has not been managed properly. 2) The Babbul Jannah Mosque in Kenali Asam Bawah Village has carried out oral transparency, namely by announcing it to the congregation about the financial reports of the mosque when Friday prayers are to be held, in writing it has also been carried out, namely by pasting the financial records of the Babbul Jannah mosque on the blackboard in the mosque. To enter into the management of the Babbul Jannah mosque, namely for the development of the economy, it can be by setting up a sweets shop, establishing a tahfiz house, establishing PAUD Raudhatul Athfal, or a people's cooperative. This is in view of the importance of the welfare economy and the continuity of a civilized life and also contributes to the growth of the embryo of Islamic Civilization.